Education governance for the twenty-first century : overcoming the structural barriers to school reform - Finn, Chester E., Jr., 1944- (Book collections on Project MUSE., 2013)
America's fragmented, decentralized, politicized, and bureaucratic system of education governance is a major impediment to school reform. In this important new book, a number of leading education scholars, analysts, and practitioners show that understanding the impact of specific policy changes in areas such as standards, testing, teachers, or school choice requires careful analysis of the broader governing arrangements that influence their content, implementation, and impact. Education Governance for the Twenty-First Century comprehensively assesses thestrengths and weaknesse.